A-G Score Associated With Outcomes in Solitary Hepatocellular Carcinoma Patients After Hepatectomy - Long, Guo; Shen, Junyi; Zhou, Ledu (Frontiers in Oncology, 2020)
Aim: the study aimed to investigate clinical significance of preoperative alpha-fetoprotein (AFP) and gamma-glutamyl transferase (GGT) (A-G score) on hepatocellular carcinoma (HCC) patients. Methods: A total of 474 solitary HCC patients was included. Survival analysis was evaluated by Kaplan-Meier method. Prognostic factors were analyzed in multivariate model. The comparison of the predictive value of AFP, GGT and A-G score was performed by receiver operating characteristic curve (ROC) analysis and decision curve analysis (DCA). Results: Of the 474 patients, 137(28.9%), 241(50.8%) and 96%(20.3%) patients were assigned to A-G score 0, 1 and 2, respectively. In multivariate analysis, A-G score, tumor size, microvascular invasion, tumor differentiation, satellite lesion and state of HBV infection were independently predictive of RFS. The A-G score could significantly stratify solitary HCC patients with distinguished prognosis. The 1-, 3- and 5-year RFS and OS among patients with A-G score 1 was better than that of patients with A-G score 2, worse than that of patients with A-G score 0(all p<0.05). Based on the result from the ROC analysis and DCA analysis, the A-G score appeared to be superior to either AFP or GGT in the prediction of prognosis of solitary HCC patients. In the subgroup analysis, the A-G score could accurately predict the prognosis of solitary HCC patients without MVI or with liver cirrhosis. Conclusions: preoperative A-G score effectively and simply predicts prognosis of solitary HCC patients after hepatectomy, especially for those with non-MVI solitary HCC or those with liver cirrhosis.